The Influence of Entrepreneurship Leadership Traits, Knowledge Sharing, and Interpretation on Business Innovation in a University: A Conceptual Paper - Lin, Angelina Vivian; Layman, Chrisanty V. (Universitas Pelita Harapan, 2023)
In a dynamic higher education landscape marked by fierce competition, the need for Entrepreneurial Leadership and Business Innovation within universities has become crucial. This study investigates how Entrepreneurial Leadership which is based on knowledge sharing and knowledge interpretation affects business innovation in an Indonesian university. This conceptual paper draws a model from past literature to study the factors influencing business innovation. The study plans to gather data from employees/lecturers/staff/leaders actively working at Pelita Harapan University (UPH) and will be analyzed using a quantitative approach and partial least squares-SEM technique. The study hopes to reveal that entrepreneurial leadership traits, such as locus of control, self-esteem, narcissism, need for achievement, and risk propensity, have direct effects on business innovation. Moreover, knowledge sharing and knowledge interpretation are two organizational learning subprocesses that play mediating roles in the relationship between entrepreneurial leadership traits and business innovation. Furthermore, the study seeks to contribute to UPH's further innovative endeavors to stay competitive and sustainable in the market.